ME1. A monoclonal antibody that distinguishes epithelial-type malignant mesothelioma from pulmonary adenocarcinoma and extrapulmonary malignancies. - O'Hara, C. J. (1990)
ME1 is a monoclonal antibody reactive in frozen tissue sections with normal mesothelial cells and malignant mesotheliomas. In this immunoperoxidase study, ME1 reacted with all 40 epithelial type malignant mesotheliomas. Fifty percent or more of the mesothelioma cells were stained in all cases and the staining intensity was strong in 32 and moderate in eight. In contrast, all 19 well- and moderately differentiated pulmonary adenocarcinomas were completely negative, and of the total 88 non-mesotheliomatous malignancies studied, staining comparable to the mesotheliomas was seen in only 6 tumors (2 pulmonary adenocarcinomas, 2 adenocarcinomas of the breast, 1 adenocarcinoma of the pancreas, and 1 melanoma), although limited, weaker staining was seen in additional cases. Five of the six strongly to moderately positive nonmesotheliomatous tumors had immunoreactivity for complementary immunoreactants (CEA, Leu-M1, S-100 protein, HMB-45). Our results with ME1, the first monoclonal antibody that recognizes malignant mesothelial cells, provides a basis for using this reagent in the differential diagnosis of tumors of the pleura and peritoneum.